Mobile technology: streamlining practice and improving care - Blake, Holly (Mark Allen Healthcare, 2013)
The use of mobile phones in care delivery has the potential to improve the way in which care is delivered. When implemented effectively, mobile technologies can empower patients and enhance communication between patients and their health-care providers. When barriers are recognised and addressed, mobile technologies can change working lives, facilitating rapid access to information and supporting efficiency in practice.